PENGARUH KUALITAS LAYANAN, NILAI NASABAH DAN ATRIBUT PRODUK ISLAM TERHADAP KEPUASAN NASABAH KOPERASI SERBA USAHA DIEFAH BANGSA PEKANDANGAN INDRAMAYU - Casriyanti, Casriyanti; Kusyana, Kusyana; Sanuri, Sanuri (Khulasah : Islamic Studies Journal, 2024)
This research wants to see the influence and relationship of service quality (X1), customer value (X2), and Islamic product attributes (X3) on customer satisfaction at the Diefah Bunga Bangsa Pekandangan Indramayu multi-business cooperative. The sampling technique used is non-probability sampling, population elements are selected on the basis of their availability (for example because they volunteer to be respondents) or because of the researcher's personal consideration that they can represent the population. This research uses purposive sampling, because it understands that the information needed can be obtained from a particular target group who are able to provide information because they do have such information and meet the specified criteria (Ferdinand, 2006). This method was chosen because it was taken based on consideration of sample criteria, namely that the sample knew information about cooperatives and was a customer of the Diefah Bunga Bangsa Pekandangan Indramayu Multi-Business Cooperative. Based on the results of inferential statistical analysis, it is stated that the three variables have a significant influence and relationship on the customer satisfaction variable, and have a significant influence. Based on the hypothesis testing stated above, it can also be concluded that there is a significant influence and relationship between the three variables on the customer satisfaction variable. This is indicated by the calculated F value being greater than the F table, as well as the calculated t value being greater than the t table